An Assistive Technology for A Deaf Student: Many-to-One System Using Button Board Speech-to-Image Based On Microcontroller ESP8266 - Kristian Dame; Lianly Rompis; Julie Rante; Ryan Singgeta (Journal of Information Technology and Its Utilization, 2024)
Education is the right of every nation and society including disable students which have physical, emotional, mental, intellectual and social disorders. In an effort to facilitate proper education for students with special needs, especially deaf students, our research team consisting of permanent lecturers from Electrical Engineering Study Program Universitas Katolik De La Salle Manado were called to care and commit to conduct research on assistive technology for deaf students. Our team designed and created a Button Board Speech-to-Image tool based on the ESP8266 microcontroller which is intended for Deaf Students to make it easier for them to communicate and interact with teachers while in class, especially during exams or learning process activities. The research method used for this research was system design and data mining. The assistive technology development method used is Research and Development (R&D). The inputs on the Button Board were processed into sound (speech) which was sent to the recipient wirelessly so that what the Deaf Student wants to convey in class can be understood by the Teacher through the speaker. The assistive technology development method used is Research and Development (R&D). The technology operates well with WiFi network and well accepted for learning process and communication.